Engineering of photo-inducible binary interaction tools for biomedical applications - Yi-Tsang Lee; Lei Guo; Tien-Hung Lan; Tatsuki Nonomura; Gan Liu; Guolin Ma; Rui Wang; Yun Huang; Yubin Zhou (Nature Communications)
Abstract The ssrA-sspB dimerization system, derived from the bacterial degradation machinery, comprises a 7-residue ssrA peptide and its binding partner sspB. The compact size of ssrA makes it ideal for insertion into proteins of interest to manipulate host protein function by engineered light-responsive sspB. In contrast to the LOV2 caging strategy employed to develop optical dimerizers, we present herein two distinct photo-inducible binary interaction tools (PhoBITs) systems: PhoBIT1, a light-OFF switch generated by integrating LOV2 into sspB, and PhoBIT2, a light-ON switch building upon an evolved ssrA/CRY2-sspB pair with minimal basal interaction. These tools enable mechanistic dissection and optogenetic modulation of GPCRs, ion channels, necroptosis, and innate immune signaling. When incorporated into a monobody, PhoBIT2 allows photo-switchable inhibition of an oncogenic fusion protein to curtail leukemogenesis in vivo. Collectively, through targeted ssrA insertions, PhoBITs offer versatile control over diverse protein functions, thereby expanding possibilities for optogenetic engineering and potential therapeutic applications.